Impact of Intertarget Distances on Single-Isocenter Radiotherapy Plans with jaw-Tracking and jaw-Fixed Techniques for Vertebral Metastases - Ling Xu MS; Huarui Yin MS; Dewen Zhang MS; Wentong Qiu MS; Xianfang Yin MS; Kai Xie MD; Xinye Ni PhD (Technology in Cancer Research & Treatment)
Introduction Multiple targets with varying distances are common in radiotherapy. Reducing treatment time in the plan design helps minimize patient movement and discomfort during the treatment process. This retrospective study aimed to investigate the impact of varying intertarget distances (ITDs) on the dosimetric differences and delivery efficiency of two single-isocenter techniques. Methods ITDs for 15 patients with dual-site vertebral metastases undergoing volume-modulated arc therapy (VMAT) were modified using Matlab 2019a. Distances of 2, 4, 6, 8, and 10 cm were considered. The VMAT plans were designed with a prescription dose of 40 Gy/20f on Infinity Linac and Monaco 5.40.01. Single-isocenter with jaw tracking (VMAT1) and fixed jaw (VMAT2) were compared in terms of dosimetry and delivery efficiency under different ITDs. Results Results showed that both VMAT plans exhibited dosimetric parameters meeting clinical requirements. The conformity index (CI) of VMAT1 plans was smaller than that of VMAT2 at ITD = 4, 6, and 8 cm (P = 0.007, 0.020, and 0.039, respectively), with no significant differences in other planning target volume dosimetry parameters. In terms of delivery efficiency, the treatment time of VMAT1 increased significantly when ITD > 2 cm compared with that at ITD = 2 cm (P = 0.000). Conversely, VMAT2 exhibited no significant change in treatment time at different ITDs (P = 0.073). For ITD = 2 cm, the treatment time of VMAT1 was shorter than that of VMAT2, with a median difference of 77 s. For ITD > 2 cm, the treatment time of VMAT2 was shorter than that of VMAT1, with a median difference ranging from 65 s to 121 s. Conclusion The experimental results showed that the single-isocenter with jaw tracking is recommended in the planning design when ITDs are less than 2 cm. However, for ITDs greater than 2 cm, the single-isocenter with fixed jaw demonstrates high delivery efficiency.5075